Financial Agency and Everyday Resilience: A Phenomenological Study of Women Entrepreneurs in Makassar’s Informal Economy - Amin, Andi Mustika (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This phenomenological study examines how women micro-entrepreneurs in Makassar’s informal economy construct and exercise financial agency amid persistent economic precarity. Grounded in a humanistic economic perspective, the research explores how women navigate financial risk and uncertainty through informal strategies, social capital, and adaptive resilience. Drawing on in-depth interviews, three superordinate themes emerged: (1) The Dual Nature of Social Capital, revealing that trust-based financial networks function simultaneously as safety nets and sources of moral burden; (2) Financial Improvisation as Agency, illustrating how women deploy creative financial practices—such as flexible budgeting and strategic concealment of profits—to retain control and autonomy; and (3) The Temporal Duality of Resilience, emphasizing the continuous oscillation between short-term survival priorities and long-term aspirations in an unstable market context. The findings demonstrate that financial decision-making in Makassar’s informal sector transcends conventional economic rationality, instead reflecting socially embedded, context-specific negotiations of agency and dependence. The study contributes theoretically to the discourse on women’s entrepreneurship by reframing financial agency as an evolving, relational process rooted in everyday resilience rather than formal inclusion. Policy implications highlight the need for human-centered interventions that recognize and strengthen women’s adaptive financial practices, mitigate the hidden costs of social capital, and support sustainable microenterprise growth in Indonesia’s informal economy.